Hubungan Stres Pada Ibu Hamil dengan Risiko Kelahiran Prematur - Anjani, Arum Dwi; Aulia, Devy Lestari Nurul; Wulandari, Nayala; Berlianti, Jihan Fia; Rahniawati, Delvitri; Adawiyah, Rabiatul; Aulia, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
Worldwide, premature birth is the leading cause of perinatal morbidity and mortality. Premature birth can be influenced by many factors, one of which is the stress experienced by pregnant women. The aim of this study is to find the relationship between the stress experienced by pregnant women and the likelihood of premature birth. This observational study with a cross-sectional design involved one hundred pregnant women in their third trimester at Hospital X. Stress levels were measured using the Perceived Stress Scale (PSS), and information about premature births was obtained from medical records. The research results indicate that there is a significant correlation between the stress levels of pregnant women and the likelihood of premature birth (p<0.05). Pregnant women with high stress levels have a greater risk than pregnant women with low stress levels of giving birth prematurely. The results show that managing stress in pregnant women is an important part of antenatal care to reduce the likelihood of premature birth.